Diagnostic Yield of Fibre-Optic Bronchoscopy in Clinically and Radiologically Suspected Cases of Bronchial Carcinoma - Mahbub, Mohammad Imtiaj; Nazneen, Shahela; Hossain, Md Ali (TAJ: Journal of Teachers Association, 2018)
Background: Bronchial carcinoma is one of the most common neoplastic disorders in which the majority of patients present at advanced stages. Fibre- optic bronchoscopy is an established investigational procedure in bronchial carcinoma, and is of paramount importance in tumor staging and hispathological typing. But there are a few studies regarding the diagnostic yield of fibre-optic bronchoscopy in our country. Methods: This was a cross-sectional study done in the respiratory medicine ward of National Institute of Diseases of the Chest and Hospital (NIDCH), Mohakhali, Dhaka from September 2011 to February 2012. All consecutive patients who were suspected clinically and radiologically as a case of bronchial carcinoma and attending in NIDCH were included in this study. There were inclusion and exclusion criteria for selecting the patients. A standard proforma and questionnaire were designed and filled up for each patient. Data was analyzed in computer using software (SPSS) and mean ± SD was applied. Results: Among the total 68 cases 56 patients (82.35%) revealed bronchial carcinoma by fibre-optic bronchoscopy (FOB). Among the 50(73.63%) patients having central lung lesion, 42(84%) patients revealed bronchial carcinoma by bronchial biopsy. Bronchial brushing was taken from 30 patients having central lung lesion and it revealed bronchial carcinoma in 18 patients( 60%). Peripheral lung lesions was found in 18 cases. Bronchial biopsy and bronchial brushing were taken in 6 cases but revealed nonspecific result. Bronchoalveolar lavage was taken in all 68 cases and revealed bronchial carcinoma in 46(67.65%) cases. Bronchial biopsy, bronchial brushing and bronchoalveolar lavage were performed on 56, 30 and 68 cases which yielded bronchial carcinoma in 42 (75%), 18 (60%) and 46 (67.65%) cases respectively. Stepwise performance of bronchial biopsy, bronchial brushing and bronchoalveolar lavage provided a diagnostic yield of 82.35% of cases who had subsequently proven bronchial carcinoma. Combined biopsy, brushing and bronchoalveolar lavage technique is more effective than single technique (P=<O.O01), which is highly significant, gives the diagnostic yield of 82.35%. Out of 50 patients having central lesion in chest X-ray the fibre-optic bronchoscopy yielded bronchial carcinoma in 45 patients (90%). But out of 18 patients having peripheral lesion in chest X-ray the fibre-optic bronchoscopy revealed bronchial carcinoma in 11 patients (61.11%). So fibre-optic bronchoscopy is more effective in the diagnosis of central mitotic lesion than peripheral mitotic lesion. The effectiveness of the combined technique (bronchial biopsy, bronchial brushing and bronchoalveolar lavage all together) is increased to 82.35%. The effectiveness is significantly lower when applied a single technique. Conclusion: By Combined bronchial biopsy, brushing and bronchoalveolar lavage 82.35% cases were diagnosed as bronchial carcinoma which is significantly higher than a single technique. Bronchoalveolar lavage may be an important diagnostic procedure in the peripheral lung lesions. TAJ 2014; 27(2): 50-57